ENGLISH FOR ISLAMIC STUDIES (EIS) - Ilzamudin Ma'mur (Al Qalam, 2005)
English jor Islamic Studies (from now on, EIS) is a kind of English for Academic Purposes that should be taken by all the students, mostly with multilingual backgrounds, at the Islamic higher educational institutions either run by the government or by private education faundations in Indonesia. One of the main of objective of EIS is to help the students improve their reading skill so as to be able to handle a variety of English written texts on "Islamic related studies. To enable both lecturers and students to achieve this objective, therefore, an appropriate syllabus and material development should be searched, for and designed comprehensively.Key Words: Curriculum, Syllabus design, Material design.